Penerapan Biosekuriti Lingkungan Kandang dalam Upaya Pencegahan Penyakit Menular - Christijanti, Wulan; Putri, Komala Amelia; Buana, Cahya; Falistina, Amna; Sriyadi, Sriyadi; Dimarti, Safira Chaerani; Mubarok, Ibnul; Herlina, Lina; Susanti, R.; Pauline, Maretha Putri (Universitas Nusantara PGRI Kediri, 2025)
Mangunsari Village is one of the goat farming centers in Gunungpati District, Semarang. They raise goats from generation to generation and based on experience, so care patterns are often not uniform from one to another. In addition to feed, animal hygiene and health are very important to implement in enforcing biosecurity in the pen and its surrounding environment. The goal of this activity is to improve goat health and the safety of the pen environment through biosecurity. The community service is divided into two: providing materials and training followed by practice. Twenty participants, members of the Mekar Sari 2 livestock farmer group, were accompanied by a team of nine lecturers, technicians, and students. The activity began with filling out a questionnaire, theory, and ended with practice. Data obtained showed that 53.8% were aged > 50 years and 23.1% were < 40 years. In addition, 84.6% of participants had been members of the livestock farmer group for a long time (≥ 10 years). There was a 0.2% increase in knowledge regarding infectious diseases, a 2% increase in leaf and grass feed, a 61.6% increase in forage that must be wilted, and a 7.7% increase in pen cleanliness. Participants also understood that forage is best not provided wet (40.5%). The results concluded that this activity improved knowledge about biosecurity components and the participants' skills in physical examination of goats and pen cleanliness.